2022
DOI: 10.5114/ko.2022.120549
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for retinopathy of prematurity: a current literature review

Abstract: Aim of the study:To present the primary and secondary risk factors for the development of retinopathy of prematurity (ROP), as reported in the literature to date. Material and methods: Analysis of scientific papers and articles available in the PubMed, Google Scholar and UpToDate databases devoted to the study of risk factors involved in the development of retinopathy in premature infants, with attention given to the WIN-ROP and G-ROP algorithms used in ophthalmic screening tests. Conclusions:The best document… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…In this Pakistani study, the ROP prevalence was 32.4% (Taqui et al, 2008). Another observational study conducted in Tehran showed that the incidence of ROP was 33.3% (Modrzejewska et al, 2022). Facts can be explained as these studies involved only deficient newborns of less than 32 weeks of birth weight.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this Pakistani study, the ROP prevalence was 32.4% (Taqui et al, 2008). Another observational study conducted in Tehran showed that the incidence of ROP was 33.3% (Modrzejewska et al, 2022). Facts can be explained as these studies involved only deficient newborns of less than 32 weeks of birth weight.…”
Section: Discussionmentioning
confidence: 99%
“…[Citation: Asian newborns are at an increased risk of severe ROP than others (Modrzejewska et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…One of the most well-known risk factors is the use of oxygen therapy in neonatal intensive care and the immaturity of preterm infants (i.e., low birth weight and early week of birth). Other, more overlooked risk factors include prenatal, perinatal, and maternal factors (i.e., methods of assisted reproduction, pregnancy-induced hypertension, thyroid diseases, gestational diabetes, chorioamnionitis and Preterm Premature Rupture of Membranes (PPROM)), and neonatal factors (mainly related to diseases of prematurity, i.e., neonatal sepsis (NS), respiratory distress syndrome (RDS), bronchopulmonary dysplasia (BPD), necrotizing enterocolitis (NEC), intraventricular hemorrhage (IVH), leukomalacia (L), and thrombocytopenia (T) [2]. Complications of this condition can pose a significant threat to the organ of vision leading to significant visual impairment and even blindness.…”
Section: Introductionmentioning
confidence: 99%